Well-being of your heart: Prevalence in depression, anxiety and psychological distress after percutaneous coronary intervention. - Torfi Már Jónsson 1990- (2022)
The aim of this study was to assess psychological distress and sociodemographic factors among Coronary Artery Disease (CAD) patients undergoing their first Percutaneous Coronary Intervention (PCI). Furthermore, to analyse if sociodemographic factors are associated with increased psychological distress. This research focuses on baseline measures for a larger study which will investigate the development of long-term psychological distress after a percutaneous coronary intervention (PCI). Data was obtained from questionnaires answered by 95 PCI patients, aged 18-75 years. Findings showed that the participant group was rather homogenous with the majority being males (79%), married or in a relationship (78%), with a secondary or university education (81%), working a full time (72%) and living in the capital area of Reykjavik (66%). Results showed that nearly half of PCI patients experienced depression symptoms (48%) and 36% experienced anxiety symptoms. Of these, 15% and 9% had moderate or severe symptoms, for depression and anxiety respectively. Analyses on psycological distress stratified by sociodemographic factors showed that PCI patients under the age of 60 experienced more anxiety symptoms (p<.001) and showed more social inhibiton (p<.05). Relationship status had an effect as well, as PCI patients who were single, divorced or widowed reported more anxiety symptoms, higher stress levels and more somatic symptoms compared with PCI patients who were married or in a relationship (all p´s <.05). No significant differences were however found in psychological distress by education level, work status or residence area. The findings of this study provide an insight into the high prevalence of depression and anxiety symptoms of CAD patients after an initial PCI procedure in Iceland, and how certain sociodemographic factors are linked with hightened psyschological distress. The results of this study draw out possible risk factors which can effect the treatment adherence and success in rehabilitation after having ...